Conflict Resolution in the Senior High Schools in Ghana and its Implications for Educational Administration: A Case Study of Ashanti Region, Ghana - Gyan, Ernest Kwabena (Journal of Education and Vocational Research, 2014)
The specific objective of this research is to look at conflict resolution in institution as being experienced in Ghanaian Senior High School. The researcher used descriptive research design to collect data from forty-three (43) Senior High Schools in the Ashanti Region of Ghana. The result indicated that when conflict is managed well, there is performance and better output; increasing effectiveness and efficiency in the school system. Despite limitations of the study, the general results depicted the core role conflict resolution plays in achieving institutional aims, objectives, aspiration and goals